"The Curse of the Caribbean"? Agency's Impact on the Productivity of Sugar Estates on St. Vincent and the Grenadines, 1814–1829. (29th June 2018) - Smith, S. D.; Forster, Martin
Abstract : This study estimates agency's impact on sugar plantation productivity using a unique early nineteenth-century panel data set from St. Vincent and the Grenadines. Results of fixed effects models, combined with a qualitative and quantitative analysis of potential endogeneity of the agency variable, provide no evidence that estates managed by agents were less productive than those managed by their owners. We discuss the results in the context of the historical and recent, revisionary, interpretations of agency, and the emergence of managerial hierarchies in the Atlantic economy.